INCREASING OF RESISTANCE OF THE THERMAL UNITS FETTLING USING BURNED MAGNESIA-CALCIC FLUX IN CONDITIONS OF ОАО «BMZ – MANAGEMENT COMPANY OF HOLDING «BMK» - I. A. Bondarenko; A. K. Turygin; A. L. Artamoshin; A. V. Vengura; A. V. Feklistov; D. V. Danilov (Литьë и металлургия, 2013)
It is shown that the use of calcined magnesia-lime flux in the Belarusian Steel Works increased the content of magnesium oxide at the average to 11.2%.